On masses of the components in SS433. Issue 4 (14th July 2018) - Cherepashchuk, A M; Postnov, K A; Belinski, A A
ABSTRACT: A huge optical luminosity of the supercritical accretion disc and powerful stellar wind in the high-mass X-ray binary SS433 make it difficult to reliably estimate the mass ratio of the binary components from spectroscopic observations. We analyse different indirect methods of the mass ratio estimate. We show that with an account of the possible Roche lobe overflow by the optical star, the analysis of X-ray eclipses in the standard and hard X-ray bands suggests the estimate q = M x / M v ≳ 0.3. We argue that the double-peak hydrogen Brackett lines in SS433 should form not in the accretion disc but in a circumbinary envelope, suggesting a total mass of M_v+M_x40 M_ . The observed long-term stability of the orbital period in SS433 |P_b/P_b|1.793× 10^-14 s −1 over ∼28 yr period is used to place an independent constraint of q ≳ 0.6 in SS433, confirming its being a Galactic microquasar hosting a superaccreting black hole.